Karakteristik pekerjaan teller di dalam melayani nasabah di era media social pada perusahaan PT. Bank Mandiri (PERSERO) di area cikini - Suryani Ganefi Sa’ud; Wilfridus B.Elu (Sekolah Pascasarjana Perbanas Jakarta, 2019)
The problems must be answered in this research is how to know about the characteristics of tellers work in the era of social media in PT. Bank Mandiri (Persero) Jakarta Cikini Area? The problem is answered through of the following questions. How does the diversity of teller to work about that skills in the social media era? How does the identity of teller work in the social media era? How does significant is the teller job in the social media era? How does the autonomy of teller work in the social media era? How does the feedback teller work in the social media era? This is research using by qualitative method is conducting direct interview (face-to-face) with teller. This research interviewed who is a teller working at PT. Bank Mandiri in Area Jakarta Cikini. The results show that the characteristics of teller work in social media era are found in the diversity of skills, task identity, task significance, task autonomy and feedback. The essence of the character of the work is in a teller who had multi tasking, choosing job priorities, prioritizing work from beginning to end, focusing on the work area, and the good interaction with the meaning of the job. So from this research, the tellers who work at this time. No longer enter at eight in the morning until four in the afternoon with a count of five working days, but seven working days in twenty-four hours. Besides that, also teller function also as Public Relation. The suggestions for future improvement is the management or the holder of the human resources authority of PT. Bank Mandiri (Persero), especially Area Jakarta Cikini, need to do deconstruction (redefinition) to the work of teller so as to accommodate the dynamics of the task of teller in the era of social media where the existing job description can be done review. In addition, education and training are continuously updated and upgraded to support the characteristics of their work in the era of social media because tellers are not only serving customers during working hours, but also functioning as public relations.